Prevalence of benign focal liver lesions and non-hepatocellular carcinoma malignant lesions in liver cirrhosis - Möller, Kathleen; Safai Zadeh, Ehsan; Görg, Christian; Dong, Yi; Cui, Xin-Wu; Faiss, Siegbert; Dietrich, Christoph F. (Zeitschrift für Gastroenterologie, 2022)
Liver cirrhosis is associated with an increased risk of developing hepatocellular carcinoma (HCC). However, other benign and malignant liver lesions may co-exist or may be the only focal liver lesion (FLL) detected. Compared to HCC, comparatively little is known about the frequency and natural history of benign FLL in patients with established liver cirrhosis.This review analyses the prevalence and frequency of benign and malignant FLL others than hepatocellular carcinoma (HCC) in liver cirrhosis including imaging and autopsy studies. Understanding these data should be helpful in avoiding misdiagnoses.
Keywords: Hämangiom; Fokal Noduläre Hyperplasie; Adenom; Leberzirrhose; HCC